Truck Drivers And Risk Of STDs Including HIV - Bansal R.K (Wolters Kluwer Medknow Publications, 1995)
Research Question: Whether long distance truck drivers are at a higher risk of contracting and transmitting STDs including HIV? Objectives: i) To study the degree of knowledge of HIV and AIDS among long- distance truck drivers. ii) Assess their sexual behaviour including condom use. iii) Explore their prevailing social influences and substance abuse patterns. iv) Explore their treatment seeking bahaviour as regards STDs. v) Deduce their risk of contracting and transmitting STDs including HIV. Study Design: Cross- sectional interview. Setting: Transport Nagar, Indore (M.P) Participants: 210 senior drivers (First drivers) and 210 junior drivers (Second drivers). Study Variables: Extra-Marital sexual intercourse, condom usage, past and present history of STDs, treatment and counseling, substance abuse, social â€" cultural milieu. Outcome Variables: Risk of contraction of STDs. Statistical Analysis: Univariate analysis. Results: 94% of the drivers were totally ignorant about AIDS. 82.9% and 43.8 % of the senior and junior drivers had a history of extra- marital sex and of these only 2 regularly used condoms. 13.8% and 3.3 % of the senior and junior drivers had a past or present history suggestive of STD infection. Alcohol and Opium were regularly used by them. Conclusion: The studied drivers are at a high risk of contracting and transmitting STDs including HIV.